INTERACTION OF TEXT, VISUALS, AND MODALITY IN CHATGPT AND JENNI AI ADVERTISEMENTS: A MULTIMODAL ANALYSIS - Puji Laksono (J-Shelves of Indragiri (JSI), 2026)
One change influenced by the development of Artificial Intelligence (AI) is the advertising strategy in online media. Generative AI platforms ChatGPT and Jenni AI have used multimodal advertising to create a technological identity, keep users interested, and build public perceptions of AI-driven productivity and creativity. This study aims to analyze the interaction of text, visual, and modality elements in ChatGPT and Jenni AI ads through a multimodal discourse analysis approach.  A qualitative descriptive method with a multimodal approach developed by Kress and van Leeuwen, focusing on representational, interactive, and compositional meaning, was used in this study. The research data used were ChatGPT digital ads and Jenni AI. The results showed that both ads utilized the complex interaction between verbal and visual elements to construct persuasive meanings. The difference is that ChatGPT ads tend to highlight futuristic innovations, universal accessibility, and technological sophistication through minimalist visual design and inclusive text strategies.In contrast, Jenni AI's ads emphasize academic productivity, writing assistance, and efficiency through formal visuals and instructional linguistic features. In addition, elements of modalities such as color composition, typography, direction of view, and interface visualization contribute greatly to building audience engagement and ideological representation. This research shows that multimodal resources are not only used as a tool of persuasion but also as an ideological mechanism that shapes the public's understanding of AI technology in contemporary digital culture. This research contributes theoretically to the development of multimodal discourse analysis in the study of AI communication and practically increases critical awareness of multimodal strategies in digital advertising.